Effects of irrigation amounts and a deficit irrigation strategy on water status and yields of intensively cultivated jojoba (Simmondsia chinensis) - Alon Ben-Gal; Shamir Badichi; Yonatan Ron; Aviad Perry; Uri Yermiyahu; Zipora Tietel; Noemi Tel Zur; Arnon Dag (Irrigation Science, 2024)
Jojoba ( Simmondsia chinensis ) is cultivated for its seeds, which contain a high-value liquid wax. There is little known regarding irrigation requirements of intensively cultivated jojoba. The project’s objectives were to evaluate the effects of irrigation regime on water status, growth, yield, and water productivity (WP, wax yield per unit of water applied) of intensely cultivated jojoba. An experiment was conducted over six years in a 14-year-old commercial plantation in Israel’s Northern Negev Desert. Treatments included: Control irrigation according to best commercial practice of returning reference evapotranspiration multiplied by a crop coefficient (Kc) of 0.5; Low irrigation providing 75% (Kc = 0.375) of the control; High irrigation providing 125% (Kc = 0.625) of the control; Regulated deficit irrigation (RDI) according to the control treatment, terminated for one to two months, after the wax accumulation stage. Stem water potential (SWP) consistently indicated jojoba water status. Increasing water application from − 25% to the control and further to + 25% led to augmented vegetative growth and number of seeds, but yield was increased at rates lower than the differences in water application by the treatments, such that WP was negatively associated. Effects on yield were limited to higher yielding ‘On’ years. The RDI treatment resulted in yield not different from the control and 15% higher WP, but significantly inhibited seed removal during mechanical harvesting. The results suggest commercial potential for increasing profits through water savings. Further research is needed to determine RDI regimes without detrimental effects on harvesting efficiency.

Instantaneous and lasting effects of drought on grapevine water use - Uri Hochberg; Aviad Perry; Shimon Rachmilevitch; Alon Ben-Gal; Or Sperling (Agricultural and Forest Meteorology, 2023)

GNI-A1 mediates trade-off between grain number and grain weight in tetraploid wheat - Guy Golan; Idan Ayalon; Aviad Perry; Gil Zimran; Toluwanimi Ade-Ajayi; Assaf Mosquna; Assaf Distelfeld; Zvi Peleg (Theoretical and Applied Genetics, 2019)